Severnaya Zemlya – geography with history at the turn of times - V. M. Kotlyakov; F. D. Zhokhov; N. V. Zhokhova; M. G. Ushakova (Лëд и снег)
100 years ago, in 1913, there was committed last geographical discovery of world importance in the Russian Arctic. Icebreaking transports «Taimyr» and «Vaygach» discovered and photographed the eastern and southern shores of the unknown land separating the Kara and Laptev seas. Boris Vilkitski Strait was opened by the north of Taimyr Peninsula as well as two small islands. Coast of the newly discovered lands received a legal name «Emperor Nicholas II Land», one of the islands was named in honor of the heir of the monarch – Tsarevich Alexei. After 1924 there was introduced the common name for a geographic feature – «Severnaya Zemlya» (North Land). Since 1926, the name «Emperor Nicholas II Land» was removed for political reasons. North shore land remained anonymous until now. In world practice (on the map of Greenland, Antarctica) the description of shores by the names of monarchs shores coexist with the common name of the main geographical object. In 1930–1932 a full examination of Severnaya Zemlya was carried out by Ushakov–Urvantsev expedition. There was found that an archipelago consists of several islands. «Not-simultaneous» shore opening and land surveying all over the archipelago led to divergent assessments of the events and facts.Preservation of historic names as a cultural and historical heritage, the inadmissibility of the historical names abolition are supported by the acting Russian Federation Law on the names of geographic features. The authors emphasize the need to return to the historical names with the application of national legislation and with justification of solutions Russian Arctic toponymy problems from international practices.